Comparative effectiveness of biologics for patients with moderate-to-severe psoriasis and special area involvement: week 12 results from the observational Psoriasis Study of Health Outcomes (PSoHO) - Piaserico, Stefano; Riedl, Elisabeth; Pavlovsky, Lev; Vender, Ronald B.; Mert, Can; Tangsirisap, Nithi; Haustrup, Natalie; Gallo, Gaia; Schuster, Christopher; Brunner, Patrick M. (Frontiers in Medicine, 2023)
Introduction Psoriasis localized at the scalp, face, nails, genitalia, palms, and soles can exacerbate the disease burden. Real-world studies comparing the effectiveness of treatments for these special areas are limited. Methods Psoriasis Study of Health Outcomes (PSoHO) is an international, prospective, non-interventional, study comparing the effectiveness of anti-interleukin (IL)-17A biologics (ixekizumab and secukinumab) compared to other approved biologics and the pairwise comparative effectiveness of ixekizumab relative to five other individual biologics for patients with moderate-to-severe psoriasis. To determine special area involvement, physicians answered binary questions at baseline and week 12. The proportion of patients who achieved special area clearance at week 12 was assessed. Missing outcome data were imputed as non-response. Comparative treatment analyses were conducted using frequentist model averaging. Results Of the 1,978 patients included, 83.4% had at least one special area involved at baseline with the scalp (66.7%) as the most frequently affected part, followed by nails (37.9%), face/neck (36.9%), genitalia (25.6%), and palms and/or soles (22.2%). Patients with scalp, nail, or genital, but not palmoplantar or face/neck psoriasis, had significantly higher odds of achieving clearance at week 12 in the anti-IL-17A cohort compared to the other biologics cohort. Patients with scalp psoriasis had a 10–20% higher response rate and significantly greater odds (1.8–2.3) of achieving clearance at week 12 with ixekizumab compared to included biologics. Conclusion Biologics demonstrate a high level of clearance of special areas at week 12 in a real-world setting. Patients with scalp, nail, or genital involvement have significantly higher odds of clearance at week 12 with anti-IL-17A biologics compared to other biologics.